Czech BEERs with PEERs: Tackling the uncertainty - Jaromír Baxa; Pavel Janécoviéc (Charles University in Prague, Institute of Economic Studies (IES), 2019)
The alternative specifications of the behavioural equilibrium exchange rate models (the BEERs) and their permanent counterparts (the PEERs) often deliver diverse estimates of the equilibrium exchange rate. In the case of the Czech koruna against the euro exchange rate, the discrepancy among the estimated BEERs often exceeds 10 %, and it had been wide before the introduction of the exchange rate commitment in November 2013 as well. Thus, the BEERs do not provide reliable guidance about the equilibrium exchange rate and the size of the equilibrium. To tackle the model uncertainty, we propose to learn about the BEERs and PEERs from the model combination to retain the information of all individual models. From a policy perspective, our results provide weak support to claims that the Czech koruna had been slightly overvalued before the introduction of the commitment in 2013. However, the koruna became increasingly undervalued since the mid of 2015, and this timing overlaps with the need to support the exchange rate commitment by the exchange rate interventions.
Keywords: F31; O24; E58; C52; 330; Equilibrium exchange rate; BEER; PEER; exchange rate commitment; model averaging